Multifactorial regulation of a Hox target gene - Stöbe, Petra; Boy, Aurelia Lara; Lohmann, Ingrid (PLoS Genetics, 2009)
Author Summary Bilateral animals share a common genetic mechanism to control development along the anterior-posterior body axis, and transcription factors of the Hox class are key regulators of this conserved process. It is thought that Hox proteins drive morphological diversification of body segments by differentially controlling the expression of downstream genes. However, due to their highly conserved DNA binding domain, the homeodomain, Hox proteins alone bind to very similar and frequently occurring sequences in the genome. This implies that Hox proteins alone are likely insufficient to activate or repress their target genes in a proper spatio-temporal fashion. In contrast to this observation, Hox proteins have very specific effects during development and execute their function with high precision. A solution to this paradox could lie in the context-specific interaction of Hox proteins with other transcriptional regulators; however, only a few examples are known. By analysing the mechanism underlying the regulation of the Hox target gene reaper, we identified a set of eight transcription factors to be important for the precise spatio-temporal regulation of this gene. Based on our findings, we suggest that Hox proteins functionally interact with a plethora of unrelated transcription factors on small, yet complex enhancer elements to execute their specific functions throughout development of diverse organisms.